Co roku to samo… Z historii orędzia noworocznego w Polsce, Niemczech i Rosji - Noińska, Marta (Przegląd Wschodnioeuropejski, 2018)
New Year’s address is one of the most conventionalized genres of political communication. The aim of the article is to describe the history of televised New Year messages of the country’s leader in Poland, Russia and Germany, with particular emphasis on the iterative motifs and signs present in their verbal and non-verbal layer. The leaders often use the same expressions, cite the same historical events, refer to the same authorities and discuss similar socio- -political issues. Moreover, montage and scenery are also subject to only slight modifications. The author also draws attention to the fact that as a ritual and conventionalized genre New Year’s address often becomes the subject of parody.